Hunger : the Biology and Politics of Starvation. - Butterly, John R. (Dartmouth College Press, 2010)
A timely and provocative look at the role political developments and the biology of nutrition play in world famine.
Keywords: Famines.; Hunger.; Malnutrition.; Starvation.; Politics, Practical.; Human rights.; Starvation; Hunger; Socioeconomic Factors; Politics; Human Rights; Environment; Malnutrition; Faim.; Inanition.; Politique.; Droits de l'homme (Droit international); starvation.; politics.; BUSINESS & ECONOMICS -- Infrastructure.; SOCIAL SCIENCE -- General.; Politics, Practical; Human rights; Famines